Learning democratic participation? Meaning-making in discussion of socioscientific issues in science education. Issue 12 (13th August 2021) - Ottander, Katarina; Simon, Shirley
ABSTRACT: Learning democratic participation as future citizens is an important goal for science education for all students. To take part in debates and decision-making involving socioscientific issues, such as sustainability, students need to become aware of different positions and dilemmas regarding such issues. This study seeks to understand how democratic participation is constructed by 45 student participants aged 16 years, for whom science is not the main course of study. Students worked in small groups on tasks that involved discussion of two different socioscientific issues. The analysis of student discourse used a theoretical perspective from discursive psychology, and shows how students deal with ideological dilemmas and resolve different positions within their discussions. Five 'interpretative repertoires' were identified from student talk illustrating the dilemmas occurring in the specific SSIs and also the function of science within the discussion. Through identifying interpretative repertoires used by the students, the stances they take and the function of science in their discussions, the study sheds light on how democratic participation can be learnt in a science education context.